2021
DOI: 10.1186/s12888-021-03299-8
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress disorder correlates among internally displaced Yazidi population following Islamic state of Iraq and Syria attacks in Iraq

Abstract: Background In 2014, the so-called Islamic State of Iraq and Syria (ISIS) took over one-third of Iraq. This study measured the rate of posttraumatic stress disorder (PTSD) among Iraqi Yazidi internally displaced persons (IDPs) and examined associated demographic and traumatic risk factors. Methods A cross-sectional survey was carried out in April–June 2015 at the Khanke camp, northern Iraq. Trauma exposure and PTSD were measured by the Harvard Traum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…Those IDP who witnessed the destruction of property were 1.67 times more likely had PTSD as compared to those who haven’t witnessed it (AOR = 1.67 [95% CI: 1.01–2.74]). The finding of this study is similar to other studies conducted in south Ethiopia and Iraq which showed that those who witnessed the destruction of personal property were 1.58 and 1.53 times more likely had PTSD than those who hadn’t experienced the destruction of personal property [ 9 , 22 ] respectively.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Those IDP who witnessed the destruction of property were 1.67 times more likely had PTSD as compared to those who haven’t witnessed it (AOR = 1.67 [95% CI: 1.01–2.74]). The finding of this study is similar to other studies conducted in south Ethiopia and Iraq which showed that those who witnessed the destruction of personal property were 1.58 and 1.53 times more likely had PTSD than those who hadn’t experienced the destruction of personal property [ 9 , 22 ] respectively.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, sex, age, and marital status had no statistically significant association with PTSD. This finding is supported by the study done in northern Uganda that showed PTSD has no association with sex and age [ 21 ], however, different from a study done in Iraq IDP that showed being a widow was a strongly significant predictor [ 22 ]. The finding of this study is different from other studies done in Ethiopia [ 9 ], Northern Uganda [ 17 ], and Mexico [ 24 ] which revealed PTSD was significantly associated with socio-demographic factors.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…7 These factors have affected a huge population in Muslim countries, especially in the Middle East and Africa, which has led to higher rates of mental illnesses among these populations. 8,9 Suicide advice and other similar topics can be found in Hadiths and the Quran. Primary, secondary, and tertiary preventative recommendations are the three kinds of instruction.…”
Section: Islamic Perspective On Suicidementioning
confidence: 99%
“…Instead of the torture and incarceration she was subjected to in her own nation of Egypt, her refuge situation may have led her to commit herself 7 . These factors have affected a huge population in Muslim countries, especially in the Middle East and Africa, which has led to higher rates of mental illnesses among these populations 8,9 …”
Section: Islamic Perspective On Suicidementioning
confidence: 99%